Nitrous oxide formation potential of various humid tropic soils of Malaysia: A laboratory study - Khalil, M.I.; Van Cleemput, O.; Rosenani, A.B.; Fauziah, C.I. (Springer, 2003)
Nitrous oxide (N2O) is formed mainly during nitrification and denitrification. Inherent soil properties strongly influence the magnitude of N2O formation and vary with soil types. A laboratory study was carried out using eight humid tropic soils of Malaysia to monitor NH4+ and NO3- dynamics and N2O production. The soils were treated with NH4NO3 (100 mg N kg-1 soil) and incubated for 40 days at 60% water-filled pore space. The NH4+ accumulation was predominant in the acid soils studied and NO3- accumulation/disappearance was either small or stable. However, the Munchong soil depicted the highest peak (238 μg N2O-N kg-1 soil d-1) at the beginning of the incubation, probably through a physical release. While the Tavy soil showed some NO3- accumulation at the end of the study with a maximum N2O flux of 206 μg N2O-N kg-1 soil d-1, both belong to Oxisols. The other six soils, viz. Rengam, Selangor, Briah, Bungor, Serdang and Malacca series, formed smaller but maximum peaks in an decreasing order of 116 to 36 μg N2O-N kg-1 soil d-1. Liming the Oxisols and Ultisols raised the soil pH, resulting in NO3- accumulation and N2O production to some extent. As such the highest N2O flux of 130.2 and 77.4 μg N2O-N kg-1 soil d-1 was detected from the Bungor and Malacca soils, respectively. The Selangor soil, belonging to Inceptisol, did not respond to lime treatment. The respective total N2O formations were 3.63, 1.92 and 1.69 mg N2O-N kg-1 soil from the Bungor, Malacca and Selangor soils, showing an increase by 49 and 99% over the former two non-limed soils. Under non-limed conditions, the indigenous soil properties, viz. Ca++ content, %clay, %sand and pH of the soils collectively could have influenced the total N2O formation.